2015
DOI: 10.1002/acs.2594
|View full text |Cite
|
Sign up to set email alerts
|

Tracking analysis of augmented complex least mean square algorithm

Abstract: The augmented complex least mean-square (ACLMS) algorithm is a suitable algorithm for the processing of both second-order circular (proper) and noncircular (improper) signals. In this paper, we provide tracking analysis of the ACLMS algorithm in the non-stationary environments. Using the established energy conservation argument, we derive a variance relation that contains moments that represent the effects of non-stationary environment. We evaluate these moments and derive closed-form expressions for the exces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…Bu sayede hem dairesel hem de dairesel olmayan kompleks-değerli verilerin ikinci-dereceden istatistiksel özelliklerin tamamı tek bir matris içerisinde değerlendirilmiştir [31][32][33][34][35][36][37][38]. Literatürde artırılmış istatistiklerin; biyomedikal, haberleşme, CASP, güç sistemleri gibi birçok farklı alanda sıklıkla kullanıldığı ve başarımı ciddi anlamda artırdığı gözlemlenmiştir [31][32][33][34][35][36][37][38][42][43][44][45][46][47][48][49][50][51][52][53]. Artırılmış istatistiğin ortaya çıkmasıyla, literatürde yer alan CASP algoritmaları; son zamanlarda kavramsal olarak kesin lineer (strictly linear, SL) ve geniş lineer (widely lineer, WL) model tabanlı algoritmalar olarak ikiye ayrılmıştır.…”
Section: Introductionunclassified
“…Bu sayede hem dairesel hem de dairesel olmayan kompleks-değerli verilerin ikinci-dereceden istatistiksel özelliklerin tamamı tek bir matris içerisinde değerlendirilmiştir [31][32][33][34][35][36][37][38]. Literatürde artırılmış istatistiklerin; biyomedikal, haberleşme, CASP, güç sistemleri gibi birçok farklı alanda sıklıkla kullanıldığı ve başarımı ciddi anlamda artırdığı gözlemlenmiştir [31][32][33][34][35][36][37][38][42][43][44][45][46][47][48][49][50][51][52][53]. Artırılmış istatistiğin ortaya çıkmasıyla, literatürde yer alan CASP algoritmaları; son zamanlarda kavramsal olarak kesin lineer (strictly linear, SL) ve geniş lineer (widely lineer, WL) model tabanlı algoritmalar olarak ikiye ayrılmıştır.…”
Section: Introductionunclassified
“…It is shown that the widely linear based adaptive filters provide a smaller mean-square error in the steady-state than that of the strictly linear algorithms [24,25]. So far different stand-alone adaptive filters have been introduced in the literature, such as the widely linear least mean square (WL-LMS) [26], augmented complex least mean square (ACLMS) [27,28], augmented affine projection [29], and widely linear recursive least squares algorithms [30]. In order to deal with three and four dimensional signals, quaternion domain adaptive filters have been developed [31][32][33].…”
Section: Introductionmentioning
confidence: 99%